Electroencephalogram (EEG) Based Fuzzy Logic and Spiking Neural Networks (FLSNN) for Advanced Multiple Neurological Disorder Diagnosis - Jain S.; Srivastava R. (My University, 2025)
Neurological disorders are a major global health concern that have a substantial impact on death rates and quality of life. accurately identifying a number of diseases Due to inherent data uncertainties and Electroencephalogram (EEG) pattern overlap, conventional EEG diagnosis methods frequently encounter difficulties. This paper proposes a novel framework that integrates FLSNN to enhance the accuracy and robustness of multiple neurological disorder disease detection from EEG signals. In multiple neurological disorders, the primary motivation is to overcome the limitations of existing methods that are unable to handle the complex and overlapping nature of EEG signals. The key aim is to provide a unified, automated solution for detecting multiple neurological disorders such as epilepsy, Parkinson’s, Alzheimer’s, schizophrenia, and stroke in a single framework. In the Fuzzy Logic and Spiking Neural Networks (FLSNN) framework, EEG data is preprocessed to eliminate noise and artifacts, while a fuzzy logic model is applied to handling uncertainties prior to applying spike neural networking to analyze the temporal and dynamics of the signals. Processes EEG data three times faster than traditional techniques. This framework achieves 97.46% accuracy in binary classification and 98.87% accuracy in multi-class classification, indicating increased efficiency. This research provides a significant advancement in the diagnosis of multiple neurological disorders using EEG and enhances both the quality and speed of diagnostics from the EEG signal and the advancement of AI-based medical diagnostics. at https://github.com/jainshraddha12/FLSNN, the source code will be available to the public. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.